(untitled) (Medical Forum Monthly, 2022)
Objective: To compare the efficacy of prophylactic vaginal progesterone with cervical cerclage in women with previous history of preterm birth. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Shahida Islam Medical and Dental College (SIMDC), Lodhran from April, 2020 to April, 2021 for a period of one year. Materials and Methods: 120 women at 14-20 weeks of gestation, who had previous history of preterm birth were included in the study. Women who had rupture of membranes, multiple pregnancy, antepartum hemorrhage and severe intra-uterine growth retardation were excluded. Progesterone pessary 200mg was given vaginally once daily at night till delivery in the Group A and McDonald’s stitch using prolene 1-0 was applied by the researchers themselves in the Group B. Effectiveness (yes/no) of both methods were noted by the researchers. Results: The mean age of women in group A was 29.97 ± 5.43 and in group B was 28.63 ± 5.12 years. Majority 68 (56.67%) were between 18 to 30 years of age. Gestational age was from 14 to 20 weeks with mean gestational age of 17.19 ± 1.97 weeks. The mean gestational age in group A was 17.13 ± 1.98 weeks and in group B was 17.23 ± 1.97 weeks. Mean parity was 2.43 ± 0.79. Mean BMI was 29.81 ± 3.11 kg/m2. Efficacy [no preterm birth (<37 weeks)] was 38 (63.33%) in group A (vaginal progesterone) and 56 (93.33%) in group B (cervical cerclage) with p-value of 0.0001. Conclusion: Conclusion was that prophylactic cervical cerclage is more efficacious than prophylactic vaginal progesterone in women with previous history of preterm birth.